Delayed Presentation of Shoulder Tuberculosis - Majid Darraj (Case Reports in Infectious Diseases)
Infections caused by Mycobacterium tuberculosis (MTb) have a global distribution, with infections occurring most frequently in persons residing in or who have resided in developing nations. Pulmonary tuberculosis (Tb) is the most common form of infection caused by MTb. Osteoarticular Tb is a far less common condition than pulmonary Tb and is frequently overlooked in the differential diagnosis of persons with joint pathology. Osteoarticular Tb infections are far less common than pulmonary Tb and are usually not considered in the differential diagnosis. We describe a case of a 57-year-old immigrant African male who presented with 5 years of right shoulder pain and a restricted range of movement. Magnetic resonance imaging (MRI) concluded right shoulder septic arthritis, for which he underwent operative drainage and debridement was undertaken. The thick purulent joint fluid subsequently yielded MTb, establishing the diagnosis of osteoarticular Tb. We conclude that Tb should be suspected in cases of long-standing joint pain and stiffness, particularly in persons from endemic areas with Tb as well as patients with a previous history of Tb exposure.